KAJIAN ALTERNATIF SISTEM JARINGAN TRANSMISI AIR BERSIH UNTUK KEBUTUHAN BANDAR UDARA BARU PROVINSI D.I YOGYAKARTA - , Helmi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
International Airport of Adisutjipto Yogyakarta is exceeds the capacity, so that needs to be developed. Based on The Feasibility Study for a new airport that has been done by PT. Angkasa Pura I, the most appropriate location for Yogyakarta new airport is Temon District, Kulon Progo Regency. One of technical requirement for airport support facilities that must be met is the provision of water supply. In order to meet these requirements is necessary a water supply transmission system. Based on investigation, there are four potential raw water sources can be utilized, namely the Sermo Reservoir, Wadaslintang Reservoir, Progo River and Bogowonto River. Airport water demand is calculated based on regulation of Dirjen Perhubungan Udara No: SKEP/77/VI/2005. Transmission pipeline is planned using Google Earth. Technical analysis using WaterNet program version 2.2 and financial analysis using NPV and BCR are done in order to obtain transmission systems from each raw water source to the new airport location. Result from that analysis obtained water supply transmission systems that are technically and financially feasible. From the calculation, water demand of the new airport at stage 3 is 2.274.682 liters/day or 26,33 liters/sec. Transmission pipeline from Sermo Reservoir is 17.215 m, Wadaslintang Reservoir 52.278 m, Progo River 24.418 m and Bogowonto River 22 547 m. Technical analysis suggests that the transmission system from Sermo Reservoir and Wadaslintang Reservoir can utilize gravity system, while from Progo River and Bogowonto River must be with pumping system. Financial analysis with interest rates 12 % and water rates Rp. 9.600 show a positive NPV (+) for all alternative transmission system, namely Sermo Reservoir is 46.247.975.639, Wadaslintang Reservoir 615.379.627, Progo River 31.994.100.031 and Bogowonto River 33.737.279.397. BCR value for all alternative transmission system shows of > 1, which Sermo Reservoir amounted to 3,37